Evapotranspiration, biomass production and water productivity acquired from Landsat 8 images in the northwestern side of the Sao Paulo state, Brazil - Teixeira, Antnio H. De C.; Leivas, Janice F.; Hernandez, Fernando B. T. [UNESP]; Franco, Renato A. M. [UNESP]; Nunez, Daniel N. C. [UNESP]; Neale, CMU; Maltese, A. (Spie-int Soc Optical Engineering, 2016)
In the northwestern side of the Sao Paulo state, Brazil, irrigated areas are expanding, because rainfall is not enough to supply the crop water requirements. Under the actual climate and land-use change scenarios, large-scale evapotranspiration (ET) and biomass production (BIO) acquirements are relevant. Eleven Landsat 8 images, from May 2013 to October 2014, were used together with a net of eight agrometeorological stations for modelling these water productivity (WP) parameters in the main agricultural growing irrigated areas inside three hydrological basins in this region. Some of these areas inside of each basin were highlighted for more in-depth WP analyses. The SAFER algorithm estimated the ratio of actual (ET) to reference (ET0) evapotranspiration and this ratio was used for both, to calculate ET and to include the soil moisture effects in the Monteith's Radiation Use Efficiency (RUE) model. The highlighted agricultural growing regions were Paranapua, Populina and Santa Rita d'Oeste in the Turvo/Grande basin; Rubineia, Santa Fe do Sul, Suzanopolis and Ilha Solteira, in the Sao Jose dos Dourados basin; and Pereira Barreto and Sud Mennucci, in the Baixo Tiete basin. The highest averages of both ET (1.7 +/- 0.9 mm d(-1)) and BIO (47 +/- 31 kg ha(-1) d(-1)) were for Ilha Solteira, while the lowest ones happened in Sud Mennucci (1.3 +/- 0.7 mm d(-1) and 40 +/- 27). These ET and BIO ranges returned WP values varying from 2.2 +/- 0.6 to 2.6 +/- 0.8 kg m(-3), with the higher end of this range happening in the Turvo/Grande hydrological basin. Considering the annual time-scale, crops will consume around 770, 828 and 786 mm yr(-1) with the corresponding BIO values of 27, 26 and 25 t ha(-1) yr(-1), respectively in Turvo/Grande, Sao Jose do Dourados and Baixo Tiete. It was concluded that increments in agricultural irrigated areas should be stimulated in the northwestern side of the state, mainly in the first basin, to retrieve good yield with less water use.
Keywords: land-use changes; irrigation; water resources; SAFER